A combination of corn gluten and soybean meal as a substitute for fishmeal in diets of turbot (Scophthalmus maximus Linnaeus, 1758) in brackish water. (23rd January 2015) - Sevgili, H.; Kurtoğlu, A.; Oikawa, M.; Aksoy, A.; Kocakaya, S.; Öztürk, E.; Uysal, R.; Gündüz Oruç, H.
Summary This study was conducted to test the replacement of fishmeal (FM) with a combination of corn gluten meal (CGM)‐soybean meal (SBM) (at a ratio of 58 : 42, respectively) fortified with lysine, taurine and monocalcium phosphate (MCP) in turbot (Scophthalmus maximus) diets. FM as the main protein source in the control diet (FM100) was replaced in 15% decrements while increasing the combination of replacement material: 85% FM (FM85), 70% FM (FM70), 55% FM (FM55) and 40% FM (FM40). The diets were fed to triplicate groups (n = 25 per group) for 9 weeks (water temperature, dissolved oxygen, pH and salinity of 18.59 ± 0.06°C, 7.32 ± 0.02 mg L−1, 7.73 ± 0.01 and 8.46 ± 0.04 g L−1, respectively). Initial weight of fish was 286.1 ± 0.1 g. At the end of the experiment, growth, feed and nutrient utilization performance of fish fed FM85 and FM70 were similar to FM100, but a further increase in plant protein led to a significant reduction of these parameters. Whole body, fillet, viscera and liver nutrient compositions were not affected significantly; however, whole body lipid levels were significantly lower in fish on FM55 and FM40 than those on FM100. The fish in–fish out ratio in the diets decreased from 2.12 in FM100 to 1.00 in FM40. The results suggest that the FM level could be reduced by 30% with a combined use of CGM‐SBM supplemented with lysine, taurine and MCP.